The Role of Ethnic Identity in the Formation of Nationalism in Post-Reformation Indonesia - Saiman, Saiman (Jurnal Ekonomi, 2022)
This study aims to analyze the role of ethnic identity in the formation of nationalism in Indonesia in the post-Reformasi period. The 1998 Reformation opened up broader spaces for expression for various ethnic groups, thus influencing the dynamics of the relationship between local and national identities. Using a qualitative approach with descriptive methods, this study combines literature review and document analysis to answer the research findings. The results indicate that ethnic identity plays a significant role in the formation of Indonesian nationalism post-Reformasi. Freedom of expression after the collapse of the New Order allowed ethnic identities to re-emerge and be recognized as part of a multicultural Indonesia, thereby strengthening a sense of national belonging. However, this dynamic is also accompanied by challenges such as social fragmentation, identity politics, and weak internalization of the values of Pancasila, tolerance, and Bhinneka Tunggal Ika (Unity in Diversity). Therefore, the formation of an inclusive nationalism requires equitable policies, strong multicultural education, and spaces for dialogue between groups to ensure that ethnic diversity becomes a unifying force, not a source of division.